2023
DOI: 10.1177/09567976231214185
|View full text |Cite
|
Sign up to set email alerts
|

Generating New Musical Preferences From Multilevel Mapping of Predictions to Reward

Nicholas Kathios,
Matthew E. Sachs,
Euan Zhang
et al.

Abstract: Much of what we know and love about music hinges on our ability to make successful predictions, which appears to be an intrinsically rewarding process. Yet the exact process by which learned predictions become pleasurable is unclear. Here we created novel melodies in an alternative scale different from any established musical culture to show how musical preference is generated de novo. Across nine studies ( n = 1,185), adult participants learned to like more frequently presented items that adhered to this rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…Musical stimuli for this study consisted of eight recorded excerpts ranging from 20 to 90 s long, that were composed in the BP scale. These included four solo-clarinet compositions that were composed by our lab for another study (Kathios et al, 2022) and excerpts from four recorded music performances that were composed for a music festival on the BP scale in 2010 (Johnson, 2010). The recorded music performances were: Reminiscences by Steven Yi, Bohlen–Pierce Pan Flute World Premiere Folk Tune by Arturo Raffaele Grolimund, Hoquetus by Johannes Kretz, and Beyond the Horizon by Georg Hajdu.…”
Section: Methodsmentioning
confidence: 99%
“…Musical stimuli for this study consisted of eight recorded excerpts ranging from 20 to 90 s long, that were composed in the BP scale. These included four solo-clarinet compositions that were composed by our lab for another study (Kathios et al, 2022) and excerpts from four recorded music performances that were composed for a music festival on the BP scale in 2010 (Johnson, 2010). The recorded music performances were: Reminiscences by Steven Yi, Bohlen–Pierce Pan Flute World Premiere Folk Tune by Arturo Raffaele Grolimund, Hoquetus by Johannes Kretz, and Beyond the Horizon by Georg Hajdu.…”
Section: Methodsmentioning
confidence: 99%
“…In their first study, Kathios et al (2023) found evidence supporting both mere exposure and predictive coding models of music preference. Specifically, participants' familiarity and liking ratings increased as a function of exposure and decreased as a function of prediction error (i.e., participants generally preferred melodies they heard more often in the exposure phase, as well as "standard" melodies over their "altered" versions).…”
Section: Music Learningmentioning
confidence: 96%
“…A mini meta-analysis of Experiments 1-4 showed that both familiarity and liking ratings exhibited quadratic relationships with exposure (meaning that familiarity and liking increased as a function of exposure up to a certain point, after which subsequent exposures had less of an impact on these ratings). Again, Kathios et al (2023) took these overall findings as evidence primarily supporting a predictive coding account of music preference formation-the effect of prediction error (i.e., higher familiarity and liking ratings for standard over "altered" melodies) was present (and actually grew in magnitude) at high exposure levels, suggesting that participants' ability to accurately predict BP musical structure played a significant role in familiarity and liking judgments of all melodies they were exposed to, even when they had been previously exposed to some of those melodies more than others. Kathios et al' (2023) mini meta-analysis also allowed them to test another hypothesis relating to music learning, preference, and individual differences-does music reward sensitivity (i.e., the extent to which individuals report feeling rewarded and/or fulfilled through music listening; Martínez-Molina et al, 2016) impact the music learning/liking trajectories described above?…”
Section: Music Learningmentioning
confidence: 98%
See 2 more Smart Citations